Aortic Valve Regurgitation: Pathophysiology and Implications for Surgical Intervention in the Era of TAVR. Issue 2 (3rd March 2020) - Ravalli, Filippo; Kossar, Alexander P.; Takayama, Hiroo; Grau, Juan B.; Ferrari, Giovanni
ABSTRACT: Aortic regurgitation (AR) or insufficiency is caused by the malcoaptation of the aortic valve (AV) cusps due to intrinsic abnormalities of the valve itself, a dilatation or geometric distortion of the aortic root, or by some combination thereof. In recent years, there has been an increase in the number of studies suggesting that AR is an active disease process caused by a combination of factors including but not limited to alteration of specific molecular pathways, genetic predisposition, and changes in the mechanotransductive properties of the AV apparatus. As the surgical management of AV disease continues to evolve, increasingly sophisticated surgical and percutaneous techniques for AV repair and replacement, including transcatheter aortic valve replacement (TAVR), have become more commonplace and will likely continue to expand as new devices are introduced. However, these techniques necessitate frequent reappraisal of the biological and mechanobiological mechanisms underlying AV regurgitation to better understand the risk factors for AR development and recurrence following surgical intervention as well as to expand our limited knowledge on patient selection for such procedures. The aim of this review is to describe some of the putative mechanisms implicated in the development of AR, dissect some of the cross-talk among known and possible signaling pathways leading to valve remodeling, identify association between these pathways and pharmacological approaches, and discuss the implications for surgical and percutaneous approaches to AV repair and replacement in the TAVR era. Abbreviations: AGAG: acidic glycosaminogylcan; AngII: angiotensin II; AR: aortic regurgitation; AV: aortic valve; BMP: bone morphogenic protein; CAVD: calcific aortic valve disease; ECM: extracellular matrix; GAG: glycosaminoglycan; HA: hyaluronic acid; LVEF: left ventricle ejection fraction; LV: left ventricle; Lpa(a): lipoprotein (a); LDL: low density lipoprotein; NAR: nuclear aspect ratio; OPN: osteopontin; 5-HT: serotonin; SLRP: small leucine-rich proteins; TenC: tenascin C; TSP-1: thrombospondin; TAVR: transcatheter aortic valve replacement; TGF-β: transforming growth factor beta; TNF- α: tumor necrosis factor alpha; VIC: valve interstitial cells, VEC: valve endothelial cells